Opioid Use by Patients After Rhinoplasty - Patel, Sagar (JAMA Facial Plast Surg, 2017)
IMPORTANCE: Given the increase in opioid addiction and overdose in the United States, reasoned opioid use after outpatient surgery may affect prescription medication abuse. OBJECTIVES: To examine patient use of opioids after rhinoplasty and establish an optimal postrhinoplasty pain management regimen. DESIGN, SETTING, AND PARTICIPANTS: In this case series, opioid use was evaluated in 62 patients who underwent rhinoplasty performed by 3 fellowship-trained facial plastic surgeons, 2 in private practice in Texas and 1 in an academic setting in Michigan, from February 2016 to September 2016. MAIN OUTCOMES AND MEASURES: Opioid use, pain control, and adverse effects were examined and opioid use was compared across patient demographic and surgical procedure characteristics, including rhinoplasty and septoplasty, open vs closed techniques, revision vs primary operations, reduction of turbinates, and use of osteotomies. Opioid use was self-reported as the number of prescribed tablets containing a combination of hydrocodone bitartrate (5 mg) and acetaminophen (325 mg) that were consumed. RESULTS: The mean (SEM) age of the patients was 38.7 (16.4) years and included 50 female patients (81%). Of the initially prescribed 20 to 30 hydrocodone-acetaminophen combination tablets, the 62 patients included in this study used a mean (SEM) of 8.7 (0.9) tablets, only 40% of those prescribed after rhinoplasty. In addition, 46 patients (74%) consumed 15 or fewer tablets, whereas only 3 patients (5%) required refills of pain medication. Sex, age, concurrent septoplasty or turbinate reduction, use of osteotomy, and history of a rhinoplasty were not associated with the number of tablets used. The most common adverse effects included drowsiness in 22 patients (35%), nausea in 7 (11%), light-headedness in 3 (5%), and constipation in 3 (5%). CONCLUSIONS AND RELEVANCE: To mitigate the misuse or diversion of physician-prescribed opioid medications, surgeons must be steadfast in prescribing an appropriate amount of pain medication after surgery. A multifaceted pain control program is proposed to manage postoperative pain and ascertain the balance between controlling pain and avoiding overprescribing narcotics. LEVEL OF EVIDENCE: NA.